Tissue-resident memory T cells in gastrointestinal tumors: turning immune desert into immune oasis - Liang, Mengjie; Wang, Xingzhou; Cai, Daming; Guan, Wenxian; Shen, Xiaofei (Frontiers in Immunology, 2023)
Tissue-resident memory T cells (Trm) are a particular type of T cell subgroup, which stably reside in tissues and have been revealed to be the most abundant memory T cell population in various tissues. They can be activated in the local microenvironment by infection or tumor cells and rapidly clean them up to restore homeostasis of local immunity in gastrointestinal tissues. Emerging evidence has shown that tissue-resident memory T cells have great potential to be mucosal guardians against gastrointestinal tumors. Therefore, they are considered potential immune markers for immunotherapy of gastrointestinal tumors and potential extraction objects for cell therapy with essential prospects in clinical translational therapy. This paper systematically reviews the role of tissue-resident memory T cells in gastrointestinal tumors and looks to the future of their prospect in immunotherapy to provide a reference for clinical application.